DEKONSTRUKSI DAN REFORMULASI TEORI PERMINTAAN DAN PENAWARAN BERBASIS NILAI SYARIAH - Rachma Febriyanti; Wahab, Abdul; Lutfi, Mukhtar; Ghalib, Muhammad (LPPM STAI Muhammadiyah Probolinggo, 2026)
This article aims to reformulate the theory of demand and supply from an Islamic economic perspective through a comparative analysis with conventional economics. Conventional theory relies on assumptions of consumer rationality, utility maximization, and a free market mechanism, which tend to overlook moral, spiritual, and social dimensions in economic behaviour. Islamic economics provides an alternative and more holistic approach by emphasizing halal–haram principles, maslahah, justice, and trustworthiness as the core of market behaviour. This research employs a literature review method by analyzing scholarly articles, books, and classical Islamic economic texts, including the works of Ibn Khaldun and Ibn Taymiyyah. Findings indicate that Islamic demand and supply theory not only explains the interaction of price and quantity but also embeds moral values and ethical guidelines in market operations. Market equilibrium in Islam is defined as a just and transparent equilibrium, free from riba, gharar, and monopoly, and strengthened by the institution of hisbah. The study concludes that an Islamic market framework promotes a more stable, just, and socially beneficial economic system.